Explicitation and Implicitation of Conjuctive Relation in Target Text of Principle Language Learning and Teaching(PLLT) - Sipayung, Kammer Tuahman; Lubis, Syahron; Setia, Edi; Silalahi, Roswita (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Explicitation, implicitation and meaning change are the kinds of cohesion shift which is the important topic to investigate in translation. The confirmation of explicitation and implicitation translation process and its devices that is adopt by Noor Cholis and Yusi Avianto Pareanom in translating conjuction activites between sentences and clauses from English (ST) to Bahasa (TT). The data of this research are several conjuction which is appear in every chapter from Principle of Language Learning Language. To prove the hypothesis of explicitation based on Blum-Kulka (1986)Â is also the aim of this research then the analysis about conjuntive relation is done based on Haliday and Hasan (1976). The result of this reaserach shown us that 1) The hypotheis is positive or the portion of explicitation is bigger (63,52%), Implicitation (28,93%), meaning change (7,54%). 2) Addition is 16 devices and omision 24 devices of conjuction are adopted by the translator. 3) translators applied explicitated to the four types of conjuction such as: additive (39,60% ), adversative (26,73% ), causal (10,89% ) and temporal (22,77%) and implicitated to the four types of conjuction additive (26,08% ), adversative (39,13% ), causal (23,91% ) and temporal (10,86%) while the meaning change on additive (66,66% ), adversative (33,33% ), causal (0% ) and temporal (0%). From the finding above, it is described that additive conjunction potrayed more explicit than other and adversative conjunction more implicit than the other while additive conjunction experiences more meaning change than the other types of conjuction.